Uterine Leiomyoma and Pregnancy Outcomes: A Retrospective Study [28D]. (May 2016) - Brantley, Jennifer; Shaw, Eric K.; Kanda, Deborah; Royek, Anthony B.
Abstract : INTRODUCTION: Research already performed has shown various adverse obstetrical outcomes associated with uterine leiomyomas. The objective of this study is aimed at examining specific perinatal outcomes associated with sonographically identified uterine leiomyomas. METHODS: This was a retrospective descriptive study of pregnant patients found to have uterine leiomyomas compared with patients without leiomyomas from 2000 to 2015 undergoing routine ultrasound examinations. Primary and secondary obstetric outcomes were obtained at delivery. Primary outcome was the risk of preterm delivery. Secondary outcomes assessed were mode of delivery, reason for cesarean section if performed, malpresentation, preterm premature rupture of membranes, and postpartum hemorrhage. Comparisons of the two groups for each of the outcome variables were examined using t test, Mann-Whitney U test, Chi-square test, or ANOVA, as appropriate. RESULTS: Of 505 women who were found to have uterine leiomyomas, 190 women had complete obstetric follow-up data. Data analysis did not show any difference in the rate of preterm delivery between the group with leiomyomas versus the group without ( P =.429). Vaginal delivery (72% compared with 28%, P =.021), planned cesarean section (68.1% compared with 31.9%, P =.005), and breech presentation (60.4% compared with 39.6%, P =.000) were significantly associated in women without leiomyomas. There was not a significant difference in the incidence of preterm premature rupture of membranes ( P =.241) or postpartum hemorrhage ( P =.801). CONCLUSION: Women with leiomyomas are not at any higher risk for obstetrical outcomes compared with women without leiomyomas.